2001
DOI: 10.1074/jbc.m002959200
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 3 Induces Gene Expression Primarily through Ras-independent Signal Transduction Pathways

Abstract: Fibroblast growth factor receptors (FGFR) are widely expressed in many tissues and cell types, and the temporal expression of these receptors and their ligands play important roles in the control of development. There are four FGFR family members, FGFR-1-4, and understanding the ability of these receptors to transduce signals is central to understanding how they function in controlling differentiation and development. We have utilized signal transduction by FGF-1 in PC12 cells to compare the ability of FGFR-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Consistent with this, here we show that, in OL progenitors, FGF-2/ FGFR1 signaling leads to proliferation and robust MAP kinase activation, whereas FGF-8/FGFR3 does not. Nevertheless, FGFR3 does induce strong signals for gene expression, primarily through Ras-independent signaling pathways in PC12 cells (Choi et al, 2001). The specific signaling pathways emerging from the activation of each FGF ligand/receptor pair in the OL lineage cells remain to be determined.…”
Section: Fgf/fgfr Specificitymentioning
confidence: 99%
“…Consistent with this, here we show that, in OL progenitors, FGF-2/ FGFR1 signaling leads to proliferation and robust MAP kinase activation, whereas FGF-8/FGFR3 does not. Nevertheless, FGFR3 does induce strong signals for gene expression, primarily through Ras-independent signaling pathways in PC12 cells (Choi et al, 2001). The specific signaling pathways emerging from the activation of each FGF ligand/receptor pair in the OL lineage cells remain to be determined.…”
Section: Fgf/fgfr Specificitymentioning
confidence: 99%
“…All FGFs act via a dual receptor system comprising four high-affinity tyrosine kinase receptors (FGFR-1 to -4) and a class of low-affinity receptors (the heparan sulfate proteoglycans) (23,24). Multiple layers of regulation control the activity of FGFs, including tissue-specific expression of ligands and receptors, modulation of binding specificity by alternative splicing of FGFRs and by sequence differences between FGFs and FGFRs, and modulation of binding affinity and specificity by heparan sulfate molecules with specific patterns of sulfation (23,(25)(26)(27). In addition to localization in the plasma membrane, FGFRs are also expressed within the nuclear envelope and matrix (28).…”
Section: Fgf-1: Key Regulator Of Human Adipogenesismentioning
confidence: 99%
“…These observations indicate that FGF and FGFR3 signaling play major roles in the regulation of bone growth. To date, four signaling pathways have been shown to propagate FGF3 signals: the STAT, MAPKextracellular signal-regulated kinase (ERK), phospholipase C-␥, and phosphatidylinositol 3-kinase-AKT pathways (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Recently, it has been shown that constitutive activation of MEK1 in chondrocytes causes Stat1-independent achondroplasia-like dwarfism in mice and rescues the FGFR3-deficient mouse phenotype (32).…”
mentioning
confidence: 99%